Kondisi vegetasi di hutan lindung Sesaot, Kabupaten Lombok Barat, Nusa Tenggara Barat, sebagai informasi dasar pengelolaan kawasan - Syamsul Hidayat (Foresty Faculty of Hasanuddin University, 2014)
The Research has been conducted in buffer zone, Sesaot Protected Forest. The aim of research is to provide information about the condition of the vegetation that covers the diversity, structure, and composition. This information is important for forest managers to maintain and even improve the composition of plant species as natural forest vegetation.Therefore, studies of forest vegetation have been conducted in two blocks (Waode and Pengkoak) using stratified sampling plots. The results indicate that the minimum curve area were found in plots of (40 x 40 m) developed in two different blocks of observations with each diversity index was 1.23 (in waode) and 1.14 (in Pengkoak). Vegetation structure in the block Waode was fairly well possessing an L-type structure, while for the block Pengkoak was somewhat less well with a U-shaped like structure. Twenty-nine plant species in Waode and 26 species on the Pengkoak were recorded with a similarity index (IS) of 0.47. The similarity index indicates that the two blocks are quite different in species composition. In the block Waode, Saurauria pendula is a dominant tree with an IVI of 107.79 followed by Debregeasia dichotoma (IVI 95.55). In contrast, in the block Pengkoak, D. dichotoma has the highest IVI, followed by Laportea decumana.